2019
DOI: 10.1186/s12917-019-1778-z
|View full text |Cite
|
Sign up to set email alerts
|

Validation of canine prostate volumetric measurements in computed tomography determined by the slice addition technique using the Amira program

Abstract: BackgroundProstatic diseases are common and mostly associated with enlargement of the accessory gland. Thus, determining the prostate size has become a main criterion for evaluating prostate health status. Computed tomography (CT) is recommended as a beneficial tool for evaluating prostate size, morphology and surrounding tissues. The purpose of this study was to establish an accurate procedure for volume estimation and afterwards evaluate the prostate volume in CT. Data of 95 dogs were analysed (58 male intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 18 publications
(60 reference statements)
8
43
1
Order By: Relevance
“…The mean volume measured by the Formula method was 41.3 cm 3 (± 141.4 cm 3 , ranging from 0.5 to 1319.8 cm 3 ) and the mean volume measured by the Wrap function was 59.8 cm 3 (± 188.7 cm 3 , ranging from 1.3 to 1579.2 cm 3 ). The SAT prostate volume values had been obtained from a previous study investigating the same dogs [5]. The mean SAT prostate volume was 58.6 cm 3 (± 188.6 cm 3 , ranging from 0.6 to 1600.5 cm 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The mean volume measured by the Formula method was 41.3 cm 3 (± 141.4 cm 3 , ranging from 0.5 to 1319.8 cm 3 ) and the mean volume measured by the Wrap function was 59.8 cm 3 (± 188.7 cm 3 , ranging from 1.3 to 1579.2 cm 3 ). The SAT prostate volume values had been obtained from a previous study investigating the same dogs [5]. The mean SAT prostate volume was 58.6 cm 3 (± 188.6 cm 3 , ranging from 0.6 to 1600.5 cm 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moss et al hypothesised that evaluation of volume provides a more accurate measurement of the organ’s size (canine liver, kidney, spleen) than measuring the organ’s length and width [16]. In a previously published paper, volumetric measurements provided more information on prostatomegaly than single dimensional parameters were able to [5]. Furthermore, it could be shown that analysing prostate volume exhibited the potential to demonstrate prostatic alterations caused by castration, age, body size and different prostatic structures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations